Properties of Bi2O3-V2O5-CaO glasses; Soviet Physics Journal; Vol. 26, № 6 - Kalygina V. M.; Kosintsev V. I. Victor Ivanovich; Gaman V. I.; Bogomolova L. D.; Modebadze O. E. (1983, 1983)
В фонде НТБ ТПУ отсутствует